Використання денормалізації реляційної бази даних з метою підвищення швидкодії запитів у системах з великим обсягом даних - Кравченко, Є. О. (ХНУРЕ, 2024)
Modern database management systems (DBMS) incorporate advanced caching, indexing and data storage optimisation technologies. However, as data volumes increase, the efficiency of query processing in relational databases decreases. While vertical scaling may be limited due to high costs, and horizontal scaling carries risks for operational projects, properly implemented denormalisation offers an effective solution for resource optimisation and performance improvement. This paper presents the results of a planned experimental study of denormalisation methods such as vertical table partitioning and summary tables.
Keywords: денормалізації реляційної бази даних; реляційна база даних; NoSQL